2023
DOI: 10.5751/es-13788-280125
|View full text |Cite
|
Sign up to set email alerts
|

Elegant conservation: reimagining protected area stewardship in the 21st century

Abstract: We present an approach to the conservation of protected areas that aligns cultural truths with scientific truths to increase community capacity for conservation. This alignment, which we call elegant conservation, asks protected area managers to reimagine how conservation can be inclusive of cultures and subcultures whose members value protected areas, but not in the same way. Reimagining how protected area managers approach conservation requires them to observe closely and holistically, with fresh eyes, human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Natural and social scientists everywhere are struggling to understand how to proceed in the face of continued biodiversity loss and the injustices brought upon people living in and around conservation landscapes (Archer et al, 2022;Bobowski & Fiege, 2023; e.g. Rudd et al, 2021;Salomon et al, 2023;Trisos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Natural and social scientists everywhere are struggling to understand how to proceed in the face of continued biodiversity loss and the injustices brought upon people living in and around conservation landscapes (Archer et al, 2022;Bobowski & Fiege, 2023; e.g. Rudd et al, 2021;Salomon et al, 2023;Trisos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…identities through the making of baskets, regalia, medicines, traditional foods, and ceremony(Hart-Fredeluces et al 2022, Oberholtzer Dent et al 2023.Because "care in power" is rooted in Indigenous sovereignty (e.g.,Whyte 2011, Simpson 2017, this concept reminds us that Indigenous Nations make resource management decisions "as an order of (Qeshm Island),Ghayoumi et al (2023) explore how governance regimes can uplift community decision making by understanding "the nature of communities, together with culture, rights, and economic interests." Writing as a park manager and scholar working in Alaska,Bobowski and Fiege (2023) discuss the challenges in resource management decision-making processes https://www.ecologyandsociety.…”
mentioning
confidence: 99%
“…Third and perhaps most important, contrasting to neoliberal PES, it is suggested that studies on ecosystem services in developing countries like Vietnam should pay more attention to stewardship than ownership, not only because nature and marginalised communities are better protected by stewardship ( van Noordwijk et al, 2010;Julian Pratts, 2011;Solazzo et al, 2015;Bobowski & Fiege, 2023), but also because the stewardship dimension is well-suited within existing social-cultural and political norms that tend to take into account the values and interests of whole society in which PES can be more easily accepted and legitimized.…”
Section: Context Mattersmentioning
confidence: 99%